Bathing Safety Management - A Case Study - Maria ADAMCZYK (Communications of International Proceedings, 2021)
The issue of safety management in bathing areas should be considered as a multifactorial phenomenon. Important for ensuring the safety of people staying in bathing areas is to provide rescue protection in the form of services and entities whose task is to undertake rescue and preventive actions in the face of a threat or event in a given area. The threat to life as a result of drowning in Poland is much higher than the average in the European Union. The standardized mortality rate is 2.2 per 100,000 population in Poland, while in other EU countries the value of the rate is between 0.4-0.6. The aim of the article is to make an analysis necessary from the perspective of management theory and practice of the existing event management system and the innovative field organization management system (SZOT) application. The system functionality was tested at the turn of 2018-2019. During the research, quantitative and qualitative data analysis based on paper and electronic reports of events filled in by Water Rescue Coordination Center (CKRW) dispatchers was used. The possibilities of the SZOT application were analyzed in terms of functionality in handling events in bathing areas. In the reporting of events, the lack of an exact GPS position defining the exact location of the event was noted, only the locality, operating region, and poviat. The implementation of a comprehensive system taking into account the available resources and risk zones, equipped with an operational analytical and communication system, will allow for a significant reduction in the response time of emergency services, and in practice will increase the chances of saving the lives of potential flood victims.
Keywords: Drowning; Technology; Management; Rescue